THE EFFECT OF INTELLECTUAL CAPITAL, BOPO, AND RETURN ON INVESTMENT ON THE CAPITAL MARKET (CASE STUDY OF CONVENTIONAL BANKS LISTED ON IDX FOR THE 2011-2020 PERIOD) - Dyah Rifda Annahlia; Anita Roowmawarni; Fauzie Senoaji (International Conference on Economics, Management, Business, and Accounting, 2024)
This paper examines the effect of Intellectual Capital, BOPO, and Return on Investment on Capital Market at Conventional Banks Listed on the IDX for the 2011-2020 period. This research method uses a quantitative approach. Data collection is done secondarily by taking data from the company's annual report on the IDX. Sample research with purposive sampling technique. The analysis tool uses Eviews10 through the following stages: Panel Data Regression Model Selection, Classical Assumption Test, Multiple Linear Regression Test, and Hypothesis Test. The results of this study indicate (1) Intellectual Capital has no significant effect on Capital Market in Conventional Banks Listed on the IDX for the Period 2011 - 2020. (2) BOPO has no significant effect on Capital Market in Conventional Banks Listed on the IDX for the 2011-2020 Period. (3) Return of Investment has a negative significant effect on Capital Market at Conventional Banks Listed on the IDX for the 2011-2020 Period. (4) Intellectual Capital, BOPO, and Return of Investment simultaneously affect the Capital Market of Conventional Banks Listed on the IDX for the 2011-2020 Period.